Behaviour of prestressed hollow core slabs strengthened with NSM CFRP strips around openings: A finite element investigation. (1st July 2021) - Elharouney, Omar; Elkateb, Mahmoud; Khalil, Ayman
Highlights: FE simulations for PHCSs with openings strengthened with NSM CFRP strips are presented. Tangential and normal traction-separation laws were utilized to capture the concrete-NSM strips bond behaviour. The developed FE models were calibrated using the experimental data. The captured overall structural behaviour closely matched with the test results. A large-scale parametric study was carried out considering several design parameters. Abstract: Prestressed Hollow Core Slabs (PHCSs) have become widely used in the construction industry owing to their economic benefits. During their service life, changes that would require openings to be situated along their spans may arise. A strengthening technique to recover or improve the original serviceability and resistances becomes indispensable. Limited research interest has been given to develop appropriate strengthening methods for the PHCSs with openings. The Near Surface Mounted (NSM) strengthening technique is among the practical and feasible solutions to rehabilitate or enhance the performance of these PHCSs. This paper demonstrates a Finite Element (FE) analysis technique to predict the responses of the PHCSs with openings, either unstrengthened or strengthened with NSM strips. The Concrete Damage Plasticity (CDP) model was successfully implemented to model the non-linear behaviour of concrete. The prestressing transmission length and the bond behaviour between the epoxy adhesive and concrete interfaces were put into practice. Acceptable agreements were found, upon validating the FE analysis results against the experimental data available in the literature. Maximum differences, compared to the experimentally attained results in the ultimate loads and the corresponding deformations of nearly 4% and −8.4%, respectively, were detected. An extensive parametric study was executed to assess the effect of various parameters on the overall behaviour of the examined slabs. The PHCS cross-sectional shape, CFRP reinforcement percentage, average precompression, opening location and size and the concrete compressive strength were taken as parameters. Above all, a gap of knowledge exits regarding the presence of design guidelines that evaluate reductions in the ultimate capacities of the PHCSs associated with the presence of openings at multiple locations along their spans and improvements experienced by employing the NSM strengthening technique. This could be bridged by utilizing the suggested modelling approach and the parametric study results in this research.